Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/polym13213790
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing with Electrical Stimulation Technologies: A Review

Abstract: Electrical stimulation (ES) is an attractive field among clinicians in the topic of wound healing, which is common yet complicated and requires multidisciplinary approaches. The conventional dressing and skin graft showed no promise on complete wound closure. These urge the need for the exploration of electrical stimulation to supplement current wound care management. This review aims to provide an overview of electrical stimulation in wound healing. The mechanism of galvanotaxis related to wound repair will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 162 publications
0
26
0
Order By: Relevance
“…Previous studies have proved that electrical stimulation can promote angiogenesis, improve blood circulation, regulate cell proliferation and differentiation, and arouse tissue remodeling in the process of trauma recovery. [82][83][84] Owing to the distinct conductivity of MXene, there are grounds to believe MXene-based nanomaterials can actively adjust the growth of skin cells and drive skin tissue regeneration. Mao et al proposed to synthesize MXene and regenerated bacterial cellulose (rBC) into composite hydrogels as wound dressings through physical and chemical dual cross-linking.…”
Section: Mxene Acts As a Conductive Materials For Wound Healingmentioning
confidence: 99%
“…Previous studies have proved that electrical stimulation can promote angiogenesis, improve blood circulation, regulate cell proliferation and differentiation, and arouse tissue remodeling in the process of trauma recovery. [82][83][84] Owing to the distinct conductivity of MXene, there are grounds to believe MXene-based nanomaterials can actively adjust the growth of skin cells and drive skin tissue regeneration. Mao et al proposed to synthesize MXene and regenerated bacterial cellulose (rBC) into composite hydrogels as wound dressings through physical and chemical dual cross-linking.…”
Section: Mxene Acts As a Conductive Materials For Wound Healingmentioning
confidence: 99%
“…Furthermore, piezoelectric descendent electric fields generated during physiological exercise provide additional bioelectrical cues to activate tendon-specific regeneration pathways ( Gouveia et al, 2017 ). Several studies have demonstrated that the motion-driven electromechanical stimulation of tendon tissue by piezoelectric bioelectric devices can regulate ion channels and affect specific tissue regeneration signaling pathways in vitro ( Cheah et al, 2021 ; Lee et al, 2021 ). Fernandez‐Yague et al (2021) studied the piezoelectric collagen nanofibrous scaffold made of arrays of nanofibers constructed from a ferroelectric material known as poly (vinylidene fluoride-co-tri-fluoroethylene) for rat AT regeneration.…”
Section: Nanofiber-based Scaffoldsmentioning
confidence: 99%
“…Relevant studies have revealed the existence of both piezoelectricity and inverse piezoelectricity in the bone, which may be key factors in the bone healing process enhanced by low-intensity biophysical–electric stimulation. Meanwhile, with the recognition of wound electrical activity as a long-lasting and regulated response, it was demonstrated that natural, endogenous electric fields and electric current could arise spontaneously after the wound of tissues, which might be necessary for the healing of defects ( Cheah et al, 2021 ; Wang et al, 2022 ). Regretfully, it is rarely found that the design, classification, and application of existing or potential bioelectric materials that can be utilized for the restoration of bone defects are systemically researched.…”
Section: Introductionmentioning
confidence: 99%